Synthesis of titanium-containing mesoporous silicas as catalysts for cyclohexene epoxidation - Elías, Verónica Rita (2009)
Ti-containing mesoporous materials have been prepared by hydrothermal synthesis at 100 °C with two different Si/Ti ratios (20 and 60) in the synthesis mixture. A detailed study about the effect of synthesis time on the physicochemical properties of the materials has been carried out. The samples were characterized by XRD, DRUVvis, N2 adsorption, and pyridine adsorption analyzed by FT-IR. The samples synthesized using the lower Si/Ti ratio presented the higher titanium incorporation and the higher acid character. The synthesis time appears as an important parameter that affects the textural, structural, chemical, and acid properties of the final solids. For the lower Si/Ti ratio, a longer synthesis time is needed to obtain a more ordered structure. However, in both cases, short synthesis times do not allow a proper incorporation of titanium into the silica framework, which is reached with synthesis times of about 3 days. The results of catalytic activity indicate that the solids studied here present an interesting potential as catalysts in the selective oxidation of cyclohexene using H2O2. © 2009 American Chemical Society.